Longitudinal Study of Motivation, Attitude, and Knowledge of Citizen Scientists Monitoring Plastic Pollution On Dutch Riverbank - Liselotte Rambonnet; Frans J. Rodenburg; Anne M. Land-Zandstra (Citizen Science: Theory and Practice, 2024)
Across the world, the number of citizen science projects focusing on plastic pollution is increasing. These projects often last for multiple years, which makes retaining volunteers challenging. However, our knowledge is limited regarding the effect of long-term involvement on citizen scientists’ motivation, attitude, and knowledge, especially for plastic pollution projects. Therefore, this study measured citizen scientists’ motivation, attitude, and knowledge in the Dutch Clean Rivers project before and during monitoring plastic pollution on riverbanks between 2017 and 2021. In total, 403 Clean Rivers participants completed a pre-survey, and a portion of them participated in one or multiple post-surveys throughout the years of monitoring. They were especially driven by Project Action motivations and Environmental motivations like tackling the source of pollution and doing something about the plastic soup, rather than being motivated by an Interest in Scientific Research like the desire to learn about scientific research. Project Action motivations increased significantly, especially within the first year of participation. Participants’ attitudes towards nature and science were initially high and did not increase significantly. Furthermore, while participants’ knowledge of plastic pollution was already high at the start, their knowledge of scientific research was not, and both increased significantly, especially in the first year of participation. The findings of this longitudinal study can contribute to improving the recruitment and retention of volunteers in current and future citizen science projects.